Integrated Assessment of Ocean Acidification Risks to Pteropods in the Northern High Latitudes: Regional Comparison of Exposure, Sensitivity and Adaptive Capacity - Bednaršek, Nina; Naish, Kerry-Ann; Feely, Richard A.; Hauri, Claudine; Kimoto, Katsunori; Hermann, Albert J.; Michel, Christine; Niemi, Andrea; Pilcher, Darren (Frontiers in Marine Science, 2021)
High latitudinal productive habitats are being increasingly exposed to the impact of ocean acidification (OA). Pelagic calcifying snails (pteropods) are found in high abundance in these regions and are a significant component of the diet of economically important fish. Pteropods have thin shells that readily dissolve at lower aragonite saturation state (Ωar), making them susceptible to ocean acidification. Here, we conducted a first integrated risk assessment for pteropods in the Eastern Pacific subpolar Gyre, including the Gulf of Alaska (GoA), Bering Sea and Amundsen Gulf. We determined the risk for pteropod populations by integrating measures of OA exposure, biological sensitivity and resilience. Exposure was based on physical-chemical hydrographic observations and regional biogeochemical model outputs, delineating seasonal and decadal changes in carbonate chemistry conditions. Biological sensitivity was evaluated based on pteropod morphometrics and shell-building processes, including shell dissolution, density and thickness. We explored resilience and adaptive capacity based on species diversity and spatial connectivity derived from the particle tracking modelling. Extensive shell dissolution was found in the central and western part of the subpolar Gyre, parts of Bering Sea and Amundsen Gulf. We identified two distinct morphotypes; L. helicina helicina with high-spired and L. helicina pacific with flatter shells. Despite the presence of different morphotypes, genetic analyses based on mitochondrial haplotypes identified a single species with no support for differentiation between the morphological forms. This coincided with the evidence for widespread spatial connectivity. We found that shell morphometrics depends on omega saturation state (Ωar); under Ωar decline, pteropods build flatter and thicker shells, which is indicative of a certain level of phenotypic plasticity. Multiple approaches identified regionally specific pteropod risks related to OA. Such integration permits improved prediction of ecosystem change relevant to effective fisheries resource management, as well as a more robust foundation for future monitoring of ecosystem health and investigation of OA in the high latitudinal habitats.